2018
DOI: 10.1109/tbme.2018.2872855
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Brain–Computer Interface Control Through Simultaneous Overt Spatial Attentional and Motor Imagery Tasks

Abstract: Objective: While noninvasive electroencephalography (EEG) based brain-computer interfacing (BCI) has been successfully demonstrated in two-dimensional (2D) control tasks, little work has been published regarding its extension to practical three-dimensional (3D) control. Methods: In this study, we developed a new BCI approach for 3D control by combining a novel form of endogenous visuospatial attentional modulation, defined as overt spatial attention (OSA), and motor imagery (MI). Results: OSA modulation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 60 publications
1
35
0
Order By: Relevance
“…1) was applied, which had successfully been applied in some previous research. [15][16][17][18][19][20][21] It is an ultra-portable device (320 x 45 x 40 mm, 145 g) that can move 25 cm horizontally, 11 cm vertically and 15 cm in-depth; it can be fitted on the monitor and uses infra camera observation and image procession to detect and follow eye movement with 60 Hz sample rate. It is easy to handle with 0.5-1 degree of visual angle and 5-or 9 point-calibration options.…”
Section: The Gazepointgp3 Eye-tracker Hardware Unitmentioning
confidence: 99%
“…1) was applied, which had successfully been applied in some previous research. [15][16][17][18][19][20][21] It is an ultra-portable device (320 x 45 x 40 mm, 145 g) that can move 25 cm horizontally, 11 cm vertically and 15 cm in-depth; it can be fitted on the monitor and uses infra camera observation and image procession to detect and follow eye movement with 60 Hz sample rate. It is easy to handle with 0.5-1 degree of visual angle and 5-or 9 point-calibration options.…”
Section: The Gazepointgp3 Eye-tracker Hardware Unitmentioning
confidence: 99%
“…The SMR or mu rhythm in EEG is generated by the synchronized electrical brain activity over the motor cortex area and has a frequency range of around 8–12 Hz ( Pfurtscheller et al, 2006 ; Bernier et al, 2007 ). In BCI applications, the frequency band centered at 12 Hz ( Royer et al, 2010 ; Doud et al, 2011 ; Cassady et al, 2014 ; Meng et al, 2016 , 2018 ; Stieger et al, 2020 ) was shown to be effective in SMR control. Event-related desynchronization (ERD) occurs when the amplitude of mu rhythm decreases in response to a person moving or imagining moving her/his body ( Pfurtscheller and Aranibar, 1979 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the BCI systems are EEG-based due to its relatively low expense, high portability, better time resolution, and minimal risks to users as compared to other modalities (Arvaneh et al, 2011 ). At present, the most extensively used brain signals for BCI input are event-related potential (ERP) (Zhang et al, 2014 ; Jin et al, 2015 , 2017 ; Yin et al, 2015 , 2016 ; Xu et al, 2018 ), steady-state visual evoked potential (SSVEP) (Pan et al, 2013 ; Wang et al, 2016 ; Xing et al, 2018 ; Zhang et al, 2018 ), and motor-imagery (MI) (Zhang et al, 2015 , 2017 ; Ang and Guan, 2017 ; Qiu et al, 2017 ; Meng et al, 2018 ; Lugo et al, 2019 ). MI-BCI works without outer stimuli, thus it is more intuitive for users (Yu et al, 2012 ; Velasco-Alvarez et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%